Oligomer formation and G-quadruplex binding by purified murine Rif1 protein, a key organizer of higher-order chromatin architecture - Moriyama, Kenji (J Biol Chem, 2018)
Rap1-interacting protein 1 (Rif1) regulates telomere length in budding yeast. We previously reported that, in metazoans and fission yeast, Rif1 also plays pivotal roles in controlling genome-wide DNA replication timing. We proposed that Rif1 may assemble chromatin compartments that contain specific replication-timing domains by promoting chromatin loop formation. Rif1 also is involved in DNA lesion repair, restart after replication fork collapse, anti-apoptosis activities, replicative senescence, and transcriptional regulation. Although multiple physiological functions of Rif1 have been characterized, biochemical and structural information on mammalian Rif1 is limited, mainly because of difficulties in purifying the full-length protein. Here, we expressed and purified the 2418-amino-acid-long, full-length murine Rif1 as well as its partially truncated variants in human 293T cells. Hydrodynamic analyses indicated that Rif1 forms elongated or extended homo-oligomers in solution, consistent with the presence of a HEAT-type helical repeat segment known to adopt an elongated shape. We also observed that the purified murine Rif1 bound G-quadruplex (G4) DNA with high specificity and affinity, as was previously shown for Rif1 from fission yeast. Both the N-terminal (HEAT-repeat) and C-terminal segments were involved in oligomer formation and specifically bound G4 DNA, and the central intrinsically disordered polypeptide segment increased the affinity for G4. Of note, pulldown assays revealed that Rif1 simultaneously binds multiple G4 molecules. Our findings support a model in which Rif1 modulates chromatin loop structures through binding to multiple G4 assemblies and by holding chromatin fibers together.